O sistema hidropônico como complemento metodológico para as aulas de Ciências - FERREIRA, Brucy Dasaiev Mendonça (2023)
Criticisms about improvements in the structure of education are constant, especially when it comes to the natural sciences. Thus, it is important to bring students closer to their reality, so that the contents they study in schools are worked on in a practical way. This work brings the theme of implementation of the hydroponic system as a complementary proposal in teaching methodologies, emphasizing its operation through the dissemination of the contents studied in chemistry, physics and biology. The proposal results from research that shows that the hydroponic system is composed of a series of properties studied in the disciplines mentioned above and focuses on: scientific concept, construction process and operation in planting techniques. Thus, it seeks to expose the contents of science, but highlighting physics, such as hydrodynamics and the way its topics can be explained using the hydroponic system. The information expressed in this work was taken from scientific articles directed to the hydroponic practice in order to prove that this technique can be used in schools, relating the functioning of the system to the studied contents, properties and characteristics. The study demonstrates that despite the hydroponic system being a planting technique, it cannot be said that it can only be worked on by biology and its specializations. It is necessary to consider the planting work as a whole, as the failure or absence of any factor can cause complications in the hydroponic system and compromise the plant's development.